Prevalence and structure of sleep disorders in neurological, psychiatric and somatic hospitals - Dmitry S. Petelin; Andrey O. Golovatyuk; Beatrice A. Volel; Mikhail Yu. Brovko; Olga Yu. Sorokina; Daria V. Troshina; Dmitri O. Rozhkov; Nikolay M. Bulanov; Paraskovya S. Sokolova; Mikhail G. Poluektov (Consilium Medicum)
Background. Today it is well known that the structure of sleep disorders and frequency of complaints about sleep disorders depend on the diseases profile. Emotional and behavioral features of patients with different disease profile are important factors affecting the development of sleep disorders.